Community Attitudes And Preferences Towards Woody Species: Implications For Conservation In Nawaikoke, Uganda - Tabuti, John R.S.; Ticktin, T.; Arinaitwe, M.Z.; Muwanika, V.B. (Oryx, 2009)
Worldwide many important tree resources, and the livelihoods of local community members who depend on them, are threatened. Effective management of tree resources requires, among other things, knowledge of which species are preferred locally and can therefore be successfully adopted into conservation plans, as well as an understanding of local attitudes towards tree conservation. We conducted a study in Nawaikoke Sub-county of eastern Uganda to address three questions: (1) Which woody species are considered most valuable to rural communities and how do priorities vary across different sectors of the communities? (2) What are local perceptions of the status of woody species and of the main threats to their conservation? (3) What attitudes do local people hold towards conservation and what challenges do conservation initiatives face? We carried out focus group discussions with different specialist groups, key informant interviews, and semi-structured interviews with 62 households. Our results illustrate that local communities value 26 woody species highly, 15 of which are indigenous. However, priorities vary greatly across different specialist user groups. According to respondents most of the prioritized species are threatened, with the greatest threats being charcoal burning, overexploitation and expanding agriculture. Community members are actively managing and/or interested in managing those tree resources with economic value but largely ignore the greater diversity of woody species, especially shrubs. Administrative, political and traditional leadership institutions do not currently assist in the conservation of woody species. We provide suggestions for a conservation action plan that involves multiple strategies.
Keywords: Agroforestry, community attitudes, conservation status, priority species, trees, Uganda, woody species.